LEGAL PROTECTION OF WORKERS/LABORERS FROM TERMINATION OF EMPLOYMENT DUE THE COVID-19 PANDEMIC AS A FORCE MAJEURE IN ORDER TO BUILD LEGAL CERTAINTY - Kurnia, Asep; Santoso, Imam Budi; Singadimeja, Holynes (Universitas Labuhanbatu, 2025)
The Covid-19 incident, many companies in Indonesia have difficulty in carrying out their activities. One of the impacts is the cessation of company activities and laying off employees. This means that many workers or laborers lose their jobs due to situations beyond the control of the company, such as this pandemic. Force majeure is an event or incident beyond human control that can affect business continuity. The purpose of this study is to analyze how legal protection for workers/laborers due to Termination of Employment on the grounds of Covid 19 as force majeure can be applied in the Karawang industrial area. This study uses the approach method. Legislation, where researchers analyze and interpret various laws that are relevant to the topic and object being studied. The results of the study show that the implementation of Termination of Employment by force majeure cannot be carried out arbitrarily, companies must maintain and make maximum efforts not to carry out Termination of Employment before finally deciding to take the route of Termination of Employment for workers/laborers. This is used as the meaning and form of legal protection carried out by the company towards employees.Keywords: Labor; COVID-19; Legal Protection; Work termination